Hypospadiology Principles and Practices - Bhat, Amilal; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book incorporates all aspects of hypospadias management, such as step-by-step correction of chordee and modifications in tabularized urethral plate repair, which is the commonest technique used in hypospadias repair, single-stage two-stage repairs of hypospadias with illustrated descriptions. It provides essential information like history, embryology, anatomy, Radiology in hypospadias, and classification of hypospadias. For the first time, this title presents separate chapters about female hypospadias, correction of torsion associated with hypospadias, and chordee without hypospadias. These chapters will improve the understanding of the subject for the reader and help them in modifying their surgical technique for these patients. Hypospadias surgery has a long learning curve, and the book will help the practitioners make them shorter. The book also deals with acute and chronic complications of surgery which will help the reader prevent complications and manage them. This is a complete book covering all aspects of the evaluation & management of hypospadias and their variants. It includes chapters on a healthy interposition and appropriate use of spongiosum and the techniques of spongioplasty, modifications in flap tube repair, along with the various types of prepuce and prepucioplasty. In conclusion, the book will provide a comprehensive read for all trainees/fellows and practitioners of Urology, Pediatric urology, Pediatric Surgery, and Plastic Surgery.
1.Hypospadias history. The long way to perfection Sameh Shehata Egypt -- 2. Hypospadias Embryology, Etiology and Classification -- 3. Anatomy of penis in hypospadias.-4.Penile Anthropometry.-.General considerations in hypospadias surgery -- 6.Chordee correction in hypospadias repair -- 7.Management options in Anterior hypospadias -- 8.Modified Tubularized incised urethral plate urethroplasty -- 9. Current status of Single stage repair in severe hypospadias -- 10. Incised plate urethroplasty in Severe hypospadias -- 11. Spongioplasty in hypospadias repair -- 12. Flaps and Grafts in hypospadias surgery -- 13. The surgical approach to 2-stage hypospadias repair -- 14. Modifications in inner prepucial flap repair of hypospadias -- 15. Management of Chordee without hypospadias.-16. Management of Female hypospadias -- 17. Management of Megmeatus Intact Prepuce -- 18. Management of Penile Torsion in hypospadias and chordee without hypospadias -- 19. Management of Iatrogenic hypospadias -- 20. Management of acute complication of hypospadias repair -- 21. Management of Late complication of hypospadias repair -- 22. Management of hypospadias Cripples -- 23. Management of hypospadias in DSD cases -- 24. Management of Penoscrotal transposition -- 25. The prepuce in hypospadias and Preputioplasty -- 26. Dressing in hypospadias repair -- 27. Psychosocial Sexual and fertility function of Hypospadiacs -- 28. Current status Evaluation of hypospadias repair results -- 29. Radiological evaluation of hypospadiacs -- 30. Evolutions in Hypospadiology and current status of tissue Engineering -- 31. Varables in hypospadias repair.
Keywords: Urology; Surgery; Urology; Surgery; Surgery; Hypospadias